Legal Study on Culinary Business Using Extreme in the Perspective of Islamic Law and National Law - Pohan, Putri Diana (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
One phenomenon that is currently rife is the practice of buying and selling food with extreme names. Food with these extreme names is already rife in the midst of society. The problem in this thesis is how are the legal provisions in the culinary business using extreme names in the perspective of Islamic law and National Law, what are the consequences of culinary business law using extreme names in the perspective of Islamic law and National Law, how is the culinary business in accordance with the rules of Islamic law and National Law. The research is a normative juridical research with a normative juridical approach using secondary data processing primary legal materials, secondary legal materials and tertiary legal materials. Analysis of the data used is qualitative data. Based on the results of the research that the legal provisions in the culinary business using extreme names in the perspective of Islamic law are not in accordance with the MUI Fatwa Number 4 of 2003 concerning the Standardization of Halal Fatwa in the fourth section regarding the problem of using names and or symbols that lead to kufr and falsehood. The legal basis for regulating the distribution of food products is Law Number 8 of 1999 concerning Consumer Protection, Law of the Republic of Indonesia Number 36 of 2009 concerning Health and Law of the Republic of Indonesia Number 18 of 2012 concerning Food and other laws and regulations. The legal consequences of the culinary business using extreme names such as using the words hell, devil, devil for the names of food products, beverages, medicines, cosmetics, and clothing because things are prohibited in Islam and the law is haram while according to Law Number 18 of 2012 concerning Food, that food and beverages that do not meet standard provisions, health requirements or endanger health are prohibited from being circulated, withdrawn from circulation, distribution permits are revoked and confiscated to be destroyed in accordance with the provisions of laws and regulations. Culinary business that is in accordance with the rules of Islamic law must be in accordance with syara' law, meaning that in the concept of Islamic law there are things that can be done and there are things that cannot be done and Islam teaches that in business you must apply the principles of business ethics while according to the consumer protection law. business actors are obliged to provide information regarding the composition of food and beverage products. Business actors who trade food and beverage products provide clear, honest information regarding the composition and halalness of traded food and beverage products to protect the rights of Muslim consumers against non-halal products.